2022
DOI: 10.3389/fpls.2022.843795
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Oxide Nanoparticles Have the Role of Alleviating Arsenic Toxicity of Barley

Abstract: Arsenic (As) contamination in agricultural soils has become a great threat to the sustainable development of agriculture and food safety. Although a lot of approaches have been proposed for dealing with soil As contamination, they are not practical in crop production due to high cost, time-taking, or operational complexity. The rapid development of nanotechnology appears to provide a novel solution to soil As contamination. This study investigated the roles of calcium oxide nanoparticles (CaO NPs) in alleviati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 49 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…CaO nanoparticles exhibit unique structural properties for common beans, so they can be exploited for soil improvement and plant fertilization. The positive effects of CaO-NPs on the growth of lettuce and zucchini (Meier et al, 2020), rice (Syu et al, 2020), chickpea (Gandhi et al, 2021), and barley (Nazir et al, 2022) have been reported. According to Gandhi et al (2021), CaO-NPs may prevent chloroplast thylakoids from being damaged and can keep cellular homeostasis during abiotic stress, which can enhance the photosynthetic activity in plants.…”
Section: Nanoparticles Enhanced Plant Growth and Increased Yieldmentioning
confidence: 99%
See 2 more Smart Citations
“…CaO nanoparticles exhibit unique structural properties for common beans, so they can be exploited for soil improvement and plant fertilization. The positive effects of CaO-NPs on the growth of lettuce and zucchini (Meier et al, 2020), rice (Syu et al, 2020), chickpea (Gandhi et al, 2021), and barley (Nazir et al, 2022) have been reported. According to Gandhi et al (2021), CaO-NPs may prevent chloroplast thylakoids from being damaged and can keep cellular homeostasis during abiotic stress, which can enhance the photosynthetic activity in plants.…”
Section: Nanoparticles Enhanced Plant Growth and Increased Yieldmentioning
confidence: 99%
“…Catalase activity of cowpea plant was significantly impacted by copper nanoparticles (Ogunkunle et al, 2018). The use of calcium nanoparticles enhanced peroxidase and catalase activities in barley seedlings, which are self-defense responses to oxidative stress (Nazir et al, 2022).…”
Section: Nanoparticles Enhanced Plant Defense Enzymes Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a scarcity of research documenting the possible functions of other metallic NPs in alleviating the damaging effects of As treatments on higher plants. Nazir et al [ 10 ] demonstrated that CaO-NPs enhanced plant growth in the presence of As toxicity by increasing calcium availability, decreasing As uptake through the downregulation of genes such as PHT1;1 , 1;3 , 1;4 , and 1;6 , and reinforcing the plant’s capacity to scavenge ROS. Li et al [ 61 ] noted that the coexistence of MnO 2 -NPs with As resulted in a decline in the average As concentration in roots and husks compared to treatments with As alone.…”
Section: Impacts Of Nps On Plants Under Hm Toxicitymentioning
confidence: 99%
“…The application of CeO 2− NPs dramatically increased plant growth and biomass, decreased oxidative stress, and promoted enzyme activity (Ma et al, 2022). Nazir et al (2022) looked into the beneficial effects of calcium oxide nanoparticles (CaO‐NPs) in reducing the toxicity caused by arsenic stress. They showed that the exogenous application of CaO‐NPs to barley ( Hordeum vulgare ) reduced the harmful effects of As stress, improved plant development, Chl content, and MDA levels, and decreased ROS production.…”
Section: Application Of Nanoparticles For Crop Improvement Against Hm...mentioning
confidence: 99%